Basketball skills & drills - Krause, Jerry 1936-; Nelson, Craig 1984- (Human Kinetics, 2019)
LeBron James and Stephen Curry can make the game appear effortless. But before those players ascended to greatness, they had to master the fundamentals in every phase of the game. As the best-selling resource in the sport, Basketball Skills & Drills has been pivotal for developing players and coaches worldwide. Now this expanded and updated fourth edition provides the perfect blueprint for building the foundation that all well-rounded players and championship teams need. Inside you'll find 103 developmental drills covering everything from stance and footwork to scoring plays and transitions. Enhanced with 42 online video clips demonstrating the drills in action, you'll have the optimal guide for mastering these fundamental skills: player positioning; moving without the ball; ballhandling and court vision; shooting; perimeter moves; post moves; rebounding. Recognizing that individual skills are effective only when used within the team concept, the book also covers team principles for both ends of the court. Tactics for offense, including special situations for out-of-bounds plays, will improve spacing, ball and player movement, shot selection, and scoring. Defensive tactics emphasize positioning, pressure, and various systems to apply in each zone of the court. To be the best, you must be fundamentally sound. Basketball Skills & Drills is your guide to becoming a dominant player with great moves and smart play